2021
DOI: 10.1002/vetr.83
|View full text |Cite
|
Sign up to set email alerts
|

NASYM, a live intranasal vaccine, protects young calves from bovine respiratory syncytial virus in the presence of maternal antibodies

Abstract: Background: Bovine respiratory syncytial virus (BRSV) is a major problem for cattle worldwide during their first year of life. The aim of the present study was to evaluate efficacy and longevity of immunity of a live vaccine (NASYM, HIPRA) in the presence of maternally derived antibodies (MDA). Method: Calves (36) were distributed in four groups, based on MDA status and treatment. They received NASYM or a placebo at an early age (less than two weeks) by intranasal route. Eight weeks later, animals were challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Other studies have reported that its prevalence within BRD is 60% in dairy cattle [18] and up to 70% in beef cattle [19]. These results are not surprising, since infection with BRSV is the major cause of BRD in cattle worldwide, especially during their first year of life [20]. Due to the nature of the service, it is difficult to classify samples by production type, so the results obtained represent both systems, dairy and beef.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other studies have reported that its prevalence within BRD is 60% in dairy cattle [18] and up to 70% in beef cattle [19]. These results are not surprising, since infection with BRSV is the major cause of BRD in cattle worldwide, especially during their first year of life [20]. Due to the nature of the service, it is difficult to classify samples by production type, so the results obtained represent both systems, dairy and beef.…”
Section: Discussionmentioning
confidence: 92%
“…Calves between one and three months of age are most susceptible to BRSV, while maternal derived antibodies (MDAs) are still present. Intranasal BRSV vaccines have demonstrated to be effective in the presence of MDAs; however, the route of administration may not be the only factor related to the efficacy of these vaccines [20]. For instance, a commercial vaccine available in Europe that can be used from the first day of life had reduced efficacy against BRSV in calves vaccinated in the presence of MDAs -according to the summary of product characteristics [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation